Experimental Investigations on Combustion Pollutant Emissions of Sunflower Biodiesel and Its Blends with Diesel and Kerosene for Furnace Application (Journal of University of Babylon for Engineering Sciences, 2018)
Biodiesel is one of the promising substitution fuels that are used in cars, gas turbine and furnace. In this study, the experiments liquid fuels used during the tests are biodiesel and its blends (biodiesel-diesel (Bx) and biodiesel-kerosene (Bkx)) in a furnace have been studied experimentally. An airblast atomizer was used to investigate the combustion properties. During the experiments, the heat rate is (12.2kW), the atomization-air to liquid fuel ratio (ALR = 1) and the constant air temperature is (301K) were maintained. For the range of equivalence ratio from 0.6 to 1.4, the characteristics of emission factors such as carbon dioxide (CO2), carbon monoxide (CO), nitrogen oxides (NOx) and unburned hydrocarbons (UbH) were measured experimentally. The results observed that the main pollutants such as CO2, CO, UbH were decreased with an increase in SME, while NOx emissions also decreased .Biodiesel could be a promising fuel for furnaces instead of fossil fuels.